Viscous Heating Effects of a Bingham Plastic Flowing Between the Parallel Plates: Investigating the Effects of Viscous Heating on Bingham Plastic Flow between Parallel Plates (Journal of Advances and Scholarly Researches in Allied Education, 2020)
In this paper, my study is about the Bingham plastic fluid model. The fluid flow between two given parallel plates, both plates are at rest has been focussed in this work. Here, It is describing the theoretical analysis of the Bingham plastic fluid model between the plates. The equation of motion, energy equation and also continuity equation are solved simultaneously at the rate of the plates are of same temperature. Incompressible Bingham plastic fluid through parallel plates and semi analytical solution has been developed and the flow behavior and temperature profiles (temperature effects) has been demonstrated and represented with respect to different parameter, as well as the dissipation terms are examined.